Expression of interferon regulatory factor 1, 3, and 7 in primary Sjögren syndrome - Zheng, Lingyan; Yu, Chuangqi; Zhang, Zhiyuan; Yang, Chi; Cai, Xieyi (Oral surgery, oral medicine, oral pathology, oral radiology and endodontics, 2009)
The aim was to investigate the level of interferon regulatory factor (IRF) 1, 3, and 7 in peripheral blood cells from patients with primary Sjogren syndrome (pSS) and to determine whether and where IRF1 exists in the parotid glands of pSS. Peripheral blood cells and parotid gland biopsy specimens from patients with pSS were studied. The IRF1, IRF3, and IRF7 gene mRNA levels in peripheral blood cells were calculated by using real-time PCR. The IRF1-positive cells in the parotid glands with pSS were observed by using immunohistochemistry and immunofluorescence . Statistical analysis was performed by Student t test. Compared with 24 control samples, the IRF1 mRNA levels in peripheral blood cells of 37 cases with pSS were up-regulated ( P < .05), but the IRF3 and IRF7 mRNA levels of pSS were not up-regulated ( P > .05). Relative quantitative levels of IRF1 mRNA were 2.17-fold higher in pSS patients than control subjects. The IRF1-positive cells of the pSS group were localized in the epithelial islands, lymphocytes, and ductal epithelial cells of the parotid glands. In all control subjects, the IRF1-positive cells were localized only to the ductal epithelial cells of parotid glands as determined by immunohistochemical staining or immunofluorescence. The scores of IRF1-positive cells of pSS were significantly higher than that of control samples ( P < .05). These findings indicate that IRF1 mRNA levels are up-regulated in the peripheral blood cells of pSS patients. Also, IRF1-positive cells exist in the epithelial islands, lymphocytes, and ductal epithelial cells of the parotid glands of individuals affected by pSS, but are limited to the ductal epithelial cells of healthy control subjects.